2021
DOI: 10.1080/15538362.2021.1918605
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Postharvest Technologies of Mango Fruit: A Review

Abstract: Mango is the third most important fruit in the tropics due to its nutritional properties and delicious flavor. The fruit is exceptionally perishable due to its climacteric nature, which decreases the quality and shelf-life. Preserving fruit quality and preventing losses during postharvest is one of the critical solutions in sustaining human dietary demands. Postharvest treatments such as 1-Methylcyclopropene, edible coatings, and hot water treatment have shown to be effective in preserving fruit quality. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 124 publications
3
12
0
1
Order By: Relevance
“…Various studies have reported the effects of chitosan-based coatings on maintaining nutrient quality and delaying the senescence of mangoes [ 3 , 5 ]. The application of polysaccharide-based coatings in combination with essential oils was an innovative strategy to maintain the postharvest quality of fruits [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the effects of chitosan-based coatings on maintaining nutrient quality and delaying the senescence of mangoes [ 3 , 5 ]. The application of polysaccharide-based coatings in combination with essential oils was an innovative strategy to maintain the postharvest quality of fruits [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Operations which are used for preserving the postharvest quality of mangoes include cold storage, modified atmospheres, radiation storage, heat treatment, chemical treatment, etc. [ 3 ]. However, some of these operations may require expensive equipment, while others may injure the quality of mangoes and affect consumer acceptance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…delaying the ripening process (Razzaq et al, 2016). Nitric oxide is also a gaseous compound that is highly reactive at extremely low concentrations (Bambalele et al, 2021). Its mechanism of action is also correlated to the inhibition of ethylene biosynthesis, resulting in a delay in the ripening process and prolonging the shelf-life of mangoes (Tran et al, 2013).…”
Section: Synthetic Reagentsmentioning
confidence: 99%
“…It showed the inhibitory effect against postharvest disease pathogens such as gloeosporioides, Alternaria, and Dothoriella spp. (Jitareerat et al, 2007;Bambalele et al, 2021). According to recent research, using chitosan at 25-75 ml/L was highly effective in delaying ripening and preserving the visual appearance and quality of HindiBesennara mango after 2 weeks of storage (Awad et al, 2017).…”
Section: Chitosanmentioning
confidence: 99%
“…The current post-harvest quarantine treatment methods commonly applied to control B. dorsalis include fumigation, radiation, insecticidal dipping, cold treatment, electromagnetic energy treatment, and hot vapor or hot water treatment [25,26]. Some of these methods have been shown to be effective depending on the host crop, albeit with challenges, including several safety-and health-related obstacles [27][28][29].…”
Section: Introductionmentioning
confidence: 99%